Cemeteries as nodes of urban green infrastructure: assessing ecological risks in war-affected areas of “Yatsevо” necropolis, Chernihiv, Ukraine: Cemeteries as nodes of urban green infrastructure: assessing ecological risks in war-affected areas of “Yatsevо” necropolis, Chernihiv, Ukraine - Lukash, Oleksandr; Morskyi, Vitalii; Strilets, Svitlana (Ecological Questions, 2026)
This study assesses the ecological transformation of the “Yatsevo” necropolis in Chernihiv, Ukraine, following intense combat operations. As a critical node of urban green infrastructure, this site represents a unique case of a memorial landscape subjected to both war-induced disturbances and anthropogenic pressure from ritual waste. We hypothesized that the combination of shell craters and unsustainable burial practices transforms the cemetery into a source of geochemical and biological risks, specifically due to contaminant migration toward the Desna River floodplain. Our multidisciplinary approach involved analyzing soil profiles from shell craters and grave walls, conducting 17 geobotanical relevés, and measuring mobile Pb and Cd via atomic absorption spectrophotometry. Results showed that 100% of samples from shell craters exceeded Pb maximum permissible concentrations (average 10.4 mg/kg). In ritual waste zones, Pb reached 28.1 mg/kg, while Cd peaked at 2.05 mg/kg, linked to polymer degradation. The flora (412 species) is highly synanthropized (59% adventive), dominated by Solidago canadensis L. (up to 98% cover). This research presents a pioneering assessment of a specific green infrastructure node–a necropolis–directly impacted by military actions in Ukraine. We conclude that post-conflict management must replace polymer ritual products with sustainable phytodesign using xerophilous perennials (Sedum L., Thymus L.) to mitigate toxicant migration.